First Five Year Plan in Bihar 1951-56 - A Review - Planning Commission (Planning Commission, 1951)
The First Five-Year Plan represented Free India’s first attempt at national reconstruction of its impoverished economy. With the achievement of independence, the demand for all-round economic regeneration was universally voiced. the First Five-Year Plan was drawn up in response to this national urge. It was by no means an ideal plan as our experience in the field was limited; but it was the first attempt towards a rational and practical assessment of our resources and our capabilities. Democratic planning has some inherent limitations. Planning techniques of such countries as have total planning have no place in a democratic set-up. In our country we have largely to depend upon the process of economic inducement rather than on economic controls. The limitation of our resources sets a further limit to any very ambitious planning.
Government of Bihar